A Design Analysis of Shell and Tube Type Recuperator in Organic Rankine Cycle Power Plant with Low-Temperature Geothermal Steam Source - MUHAMMAD RIFQI DWI SEPTIAN; Fitri Rusmaladewi; Friska Hasugian; Rozi Afdi; Dwi Miftha Kurnia; Stevy Canny Louhenapessy; Randy Yusuf Kurniawan; Setiadi Wira Buana (Journal of Petroleum and Geothermal Technology, 2025)
Organic Rankine Cycle (ORC) power generation systems offer an effective means to harness low-grade geothermal heat. A crucial component in improving ORC thermal performance is the recuperator, which recovers residual heat from the turbine outlet to preheat the working fluid. This study focuses on the design and evaluation of a shell and tube recuperator using R-600a as the working fluid, through thermodynamic and heat transfer analyses. Key parameters such as LMTD (32.38 °F), effectiveness (0.434), and heat transfer area (60.35 m²) were calculated. Pressure drops were within acceptable limits (tube side: 4.46 psi; shell side: 0.475 psi), and the dirt factor of 0.0038 indicates good resistance to fouling. The results support the feasibility of implementing the proposed design in small to medium-scale geothermal ORC applications. Keywords: geothermal; ORC; recuperator; shell and tube; thermal analysis